Pengaruh Budaya Organisasi, Intregritas Dan Loyalitas Terhadap Kinerja Karyawan Bank Bri Unit Tubei Kanca Curup - novella, Tressa rud; Fauzan, Markoni, (Jurnal Mirai Management, 2024)
To find out how big the influence of Organizational Culture is on Employee Performance, the Influence of Integrity, the Influence of Loyalty at Bank BRI Tubei Kanca Curup Unit. This research uses data collection techniques by distributing questionnaires, the sampling technique is using saturated or proballty sampling techniques. This research uses an approach quantitative which is explanatory in nature. There is an influence of organizational culture (X1) on employee performance (Y) BRI Bank Store Tubei Kanca Curup Unit with a value of tsig < α (0.001 ttable (2.571> 1.68107) with Thus, Ho is rejected and Ha is accepted. There is an influence of integrity (X2) on employee performance (Y) at the BRI Bank Store, Tubei Kanca Curup Unit with a value of tsig < α (0.004 ttable (2.571> 1.68107) Thus Ho is rejected and Ha is accepted. There is an influence of loyalty (X3) on employee performance (Y) of the BRI Bank Shop Tubei Kanca Curup Unit with a value of tsig < α (0.003 ttable (2.571> 11.68107) thus Ho is rejected and Ha accepted. Keywords : Influence of Organizational Culture, Integrity and Loyalty